Magnesium and aluminum sulfates in salt efflorescences from acid mine drainage in the Iberian Pyrite Belt (SW Spain) - Valente, Teresa Maria Fernandes (2016)
Proceedings IMWA 2016, Freiberg/Germany | Drebenstedt, Carsten, Paul, Michael (eds.) | Mining Meets Water – Conflicts and Solutions.